The Genetic Architecture of Post-Zygotic Reproductive Isolation Between Anopheles coluzzii and An. quadriannulatus - Deitz, Kevin C.; Takken, Willem; Slotman, Michel A. (Frontiers in Genetics, 2020)
The Anopheles gambiae complex is comprised of eight morphologically indistinguishable species and has emerged as a model system for the study of speciation genetics due to the rapid radiation of its member species over the past two million years. Male hybrids between most An. gambiae complex species pairs are sterile, and some genotype combinations in hybrid males cause inviability. We investigated the genetic basis of hybrid male inviability and sterility between An. coluzzii and An. quadriannulatus by measuring segregation distortion and performing a QTL analysis of sterility in a backcross population. Hybrid males were inviable if they inherited the An. coluzzii X chromosome and were homozygous at one or more loci in 18.9 Mb region of chromosome 3. The An. coluzzii X chromosome has a disproportionately large effect on hybrid sterility when introgressed into an An. quadriannulatus genetic background. Additionally, an epistatic interaction between the An. coluzzii X and a 1.12 Mb, pericentric region of the An. quadriannulatus 3L chromosome arm has a statistically significant contribution to the hybrid sterility phenotype. This same epistatic interaction occurs when the An. coluzzii X is introgressed into the genetic background of An. arabiensis, the sister species of An. quadriannulatus, suggesting that this may represent one of the first Dobzhansky–Muller incompatibilities to evolve early in the radiation of the Anopheles gambiae species complex. We describe the additive effects of each sterility QTL, epistatic interactions between them, and genes within QTL with protein functions related to mating behavior, reproduction, spermatogenesis, and microtubule morphogenesis, whose divergence may contribute to post-zygotic reproductive isolation between An. coluzzii and An. quadriannulatus.